CORRELATION OF TRANSVERSAL DIMENSIONS OF THE JAWS AND SAGITTAL CHARACTERISTICS OF THE DENTAL ARCH WITH ODONTOMETRIC AND CEPHALOMETRIC INDICES IN BOYS WITH ORTHOGNATHIC BITE - Маrchenko А.V. (World of Medicine and Biology, 2017)
The article describes and analyzes the correlation of computer-tomographic characteristics of dental arcs with odontometric and cephalometric characteristics in boys with orthognathic bite. The greatest number of correlations of the size of the teeth with transversal dimensions of the upper and lower jaw are established with mesiodistal dimensions of the crowns of teeth (48.6%), vestibule-tongue sizes crowns of teeth (42.4%) and the width of the dentin-enamel border in the vestibule-tongue direction (41,7%); with the parameters of the maxillary dental arches in the sagittal plane - a similar distribution is maintained (69.4% with mesiodistal crowns of teeth, 80.6% with vestibule-tongue sizes crowns of teeth, 77.8% with the width of the dentin-enamel border in the vestibule-tongue direction ); with the parameters of the maxillary dental arc in the vertical plane there is a completely different distribution - the greatest number of correlations is established only with the width of the dentin-enamel border in the vestibule-tongue direction (22,2%). In analyzing the correlations of cephalometric indices in the general groups of boys, almost identical numbers with the transversal dimensions of the upper and lower jaw and the parameters of the maxillary dental arc in the vertical plane (24.8 and 25.7% respectively) and only 8.6% with the parameters of the maxillary dental arcs in the sagittal plane.